Fuzzy-Ga Combined Approach in Image Encryption - Das, Subhajit; Mandal, SatyendraNath; Karforma, Sunil (International Journal of Computer Sciences and Engineering, 2025)
Many algorithms have been developed to encrypt digital image. In this paper Fuzzy set theory in combination with genetic algorithm has been applied to encrypt the image. Genetic algorithm is used for key generation and fuzzy set theory has been used to diffuse original image .The encrypted image is obtained after logical operation between the key set and diffused image. A number of tests have been applied on encrypted image to check the security level of the proposed algorithm.